Die liefde van God as aanknopingspunt vir ’n gesprek met Moslems: die rol van Joh. 3:16 - Verster, P. (Faculty of Theology, University of the Free State, 2009)
Christian and Muslim relations are under tremendous strain. The political situation makes it very difficult to proclaim the love of God to Muslims. It is, however, possible to reach out to Muslims from the explanation of the love of God. John 3:16 is of utmost importance in this regard. In this article the love of God for the whole world is portrayed and in his love He reaches out to all and not only to Israel. The difficult concept of “Son of God” must, however, be explained to Muslims who often are offended by the concept because of a biological understanding of it. The confession of the Trinity is of importance to fully explain the love of God and must be proclaimed in the dialogue with and the proclamation of the Gospel to Muslims.
Keywords: Love; Son of God; Muslims; Dialogue